Save the white whale! - Stilton, Geronimo. (Geronimo Stilton., 2011)
"I invited my friend Petunia Pretty Paws to visit the Bay of Whales with me. But our trip got off on the wrong paw, and my relaxing vacation turned into a real nightmare. That is, until Petunia and I came across a great white whale that needed our help" (publisher).